Analysis of workplace facilities in the Remuneration and Industrial Relations (RHI) Department using anthropometric approach - Mursyid, Ahmad Dani; Fasa, Nadia; Nugraha, Billy (Journal Industrial Servicess, 2023)
In the industrial landscape, employee welfare plays a pivotal role in influencing company productivity and overall employee satisfaction. A crucial aspect that shapes employee welfare is the quality of the work facilities provided by the company. The incorporation of ergonomic work facilities can significantly amplify work comfort and safety, thereby mitigating the risks associated with work-related injuries or health issues. This research seeks to assess the ergonomic aspects of work facilities within a workspace by applying anthropometric principles. This methodology involves measuring various facets of the human body, encompassing shape, size, and strength, and utilizing these metrics to customize facilities to suit human requirements. Such an approach holds the potential to augment employee performance and alleviate symptoms associated with musculoskeletal disorders. The research findings highlight several dimensions of work facilities that do not align with the employees' body dimensions. Consequently, it is imperative to propose recommendations to the Remuneration and Industrial Relations Department of PT CCP, a private company in Indonesia, aimed at enhancing work facilities. These suggestions aim to realign the facilities with anthropometric dimensions meticulously designed by the author.